2020
DOI: 10.1097/mpa.0000000000001521
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Pancreatic Cancer and the Necessity of Long-Term Surveillance in Patients With Pancreatic Cystic Lesions

Abstract: Objectives Pancreatic cystic lesions (PCLs) are a risk factor for pancreatic cancer (PC). Which PCLs should be surveilled and necessity of long-term observation are still controversial. Methods From January 2000 to March 2016, we enrolled 1137 patients with PCLs observed for 1 year. We defined PCLs with cyst size of greater than 30 mm, main pancreatic duct (MPD) of greater than 5 mm or mural nodule as high-risk group, and others as low-risk group (LRG).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…DM is prevalent in patients with IPMN [ 26 , 27 ], and Capurso G et al reported an odds ratio (OR) of 1.79 (95% CI, 1.08–2.98) for IPMN in diabetic patients [ 26 ]. In addition, DM is reported to be associated with degree of dysplasia of IPMN [ 28 , 29 , 30 ]. Morales-Oyarvide V et al reported that the OR for high grade dysplasia (HGD) and invasive carcinoma among diabetic patients was 2.02 (95% CI, 1.02–4.01) and 2.05 (95% CI, 1.08–3.87), respectively [ 28 ].…”
Section: New-onset Diabetes Mellitus As a Clue For Early Diagnosismentioning
confidence: 99%
“…DM is prevalent in patients with IPMN [ 26 , 27 ], and Capurso G et al reported an odds ratio (OR) of 1.79 (95% CI, 1.08–2.98) for IPMN in diabetic patients [ 26 ]. In addition, DM is reported to be associated with degree of dysplasia of IPMN [ 28 , 29 , 30 ]. Morales-Oyarvide V et al reported that the OR for high grade dysplasia (HGD) and invasive carcinoma among diabetic patients was 2.02 (95% CI, 1.02–4.01) and 2.05 (95% CI, 1.08–3.87), respectively [ 28 ].…”
Section: New-onset Diabetes Mellitus As a Clue For Early Diagnosismentioning
confidence: 99%
“…These characteristics, either referred to as worrisome features (WFs) and high‐risk stigmata (HRS) in the international Fukuoka criteria, or as relative and absolute indications for surgery in the European guidelines, prompt for intensified surveillance or surgical resection 13,14 . In contrast, BD‐IPMNs without these features at diagnosis have a low risk of malignancy, 11,15,19,21–24 which decreases to less than 1% after several years of unremarkable follow‐up 15,22 …”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer (PC) is one of the most aggressive malignant diseases, with a 5-year survival rate of 9 % 1 . Because it is difficult to detect PC at an early stage 2 3 , the majority of patients with it are diagnosed when the disease is unresectable and they primarily undergo chemotherapy 4 5 . Combination chemotherapy regimens have become the standard first-line chemotherapy in patients with unresectable PC.…”
Section: Introductionmentioning
confidence: 99%